Atraumatic Splenic Rupture Associated with Influenza A (H1N1) Pneumonia: Case Report and Review of the Literature - Dilraj Deol; Huimin Wu; Anayansi Lasso-Pirot; Kathryn S Robinett; Montserrat Diaz-Abad (Case Reports in Medicine)
Influenza virus infection may present with fever, chills, headache, myalgia, malaise, and respiratory symptoms, with a few cases developing into pneumonia, respiratory failure, and other organ damage. Very few cases of atraumatic splenic rupture associated with influenza infection have been reported. Atraumatic splenic rupture, while rare, is associated with high mortality. Here, we report the first case of atraumatic splenic rupture associated with influenza infection in the English literature and review the prior reported literature. The patient was diagnosed with influenza A (H1N1) pneumonia and subsequently developed hemorrhagic shock requiring emergency laparotomy and removal of the ruptured spleen.